2019
DOI: 10.15296/ijwhr.2021.20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-marital Sexual Counseling on Self-efficacy and Sexual Function of Iranian Newlywed Women

Abstract: Objectives: Sexual health counseling and education are important parts of pre-marital counseling programs, which can play effective roles in the prevention of sexual dysfunction and an increase in marital satisfaction. In this regard, this study aimed to assess the effect of the pre-marital sexual counseling of couples on self-efficacy and sexual function among females who referred to pre-marital training courses in Zahedan, Iran. Materials and Methods: This quasi-experimental study was conducted on 110 couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Women that were counselled on marital sexual relationships prior to their marriage had high sexual satisfaction mean score compared to those that were not. Earlier, 7,10,13 reported that marital/ sexual health-focused premarital counselling improves sexual satisfaction among couples. 6 recommend development of premarital counselling and continuous educational programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women that were counselled on marital sexual relationships prior to their marriage had high sexual satisfaction mean score compared to those that were not. Earlier, 7,10,13 reported that marital/ sexual health-focused premarital counselling improves sexual satisfaction among couples. 6 recommend development of premarital counselling and continuous educational programs.…”
Section: Discussionmentioning
confidence: 99%
“…11 Premarital counselling raises levels of a couple’s sexual health knowledge. 12 Among newlywed Iranian women in a quasi-experimental study, 13 reported that sexual health-focused premarital counselling and educational intervention help in improving marital relationships of the couples.…”
Section: Introductionmentioning
confidence: 99%